Adapted educational health program among deprived subjects with prediabetes. Issue 5 (October 2022) - Thomas, F.; Pannier, B.; Meghiref, K.; Galtier, D.; Lamande, JP; Raison, J.; Danchin, N.
Abstract: Aims: Assess the feasibility and benefit of a health educational program on global metabolic status in prediabetic deprived subjects. Design: Case control study. Methods: 693 subjects (466 men, 227 women), aged 16 to 95 years with prediabetes and low socioeconomic status, consulting at the IPC Center were included between September 2015 and June 2016. Subjects were invited to participate in 4 workshops (2 nutrition, 2 physical activities). One year after their inclusion (visit 1), they were offered a second health check-up (visit 2). Participants were classified into 3 groups: 1) Intervention group (INTG, N=133): complete process 2) Control group (CG, N=415): Only a second health check-up, no workshop participation; 3) Abandoned group (AG, N=145). All groups were compared. Results: After considered confounding factors, fasting blood glucose and SBP levels variation between visit 1 and visit 2 differed significantly between the CG and INTG. In the INTG with higher diminution of fasting glucose, 90% reported eating healthy food since nutrition workshop and 51%. reached objectives (The same trend was observed for physical activity. Conclusion: An educational program among deprived prediabetic tended to limit fasting glucose increment, improve metabolic status and encourage healthy lifestyle despite difficulties in convincing subjects to participate. Highlights: A minimal educational program among deprived prediabetic subjects. Limit diabetes. Improve metabolic status. Encourage a lifestyle aimed to limit cardiovascular and diabetes risk factors. Show difficulties to convince deprived subjects to participate to Health education.